PENGEMBANGAN SOFTWARE âVIRTUAL AJI SAKAâ SEBAGAI ALAT BANTU UNTUK BELAJAR MENGENAL AKSARA JAWA DENGAN PENDEKATAN MULTIMEDIA - Affandi, Luqman (DINAMIKA DOTCOM, 2012)
Based on these facts, the original Indonesia culture is increasingly fell under the influence of a foreign culture. It affects the young generation of Indonesia began reluctant to explore the work of our ancestors. One example of the many who do not master the java script. The difficulty level of understanding learning Java script is quite difficult.Therefore, it is necessary that new breakthroughs in learning Java script easier. One attempt to do is to create an interactive learning using computer technology.Problems encountered in the development of Javanese Javanese is the application of the algorithm into a computer algorithm. In addition, to improve the ease of learning needs to be done towards the development of multimedia applications. This effect on the increase in the algorithms used.Â Key words: Virtual, Aji Saka, Java Script, Multimedia